Cellular and Site-Specific Mitochondrial Characterization of Vital Human Amniotic Membrane. Issue 1 (January 2018) - Banerjee, Asmita; Lindenmair, Andrea; Hennerbichler, Simone; Steindorf, Philipp; Steinborn, Ralf; Kozlov, Andrey V.; Redl, Heinz; Wolbank, Susanne; Weidinger, Adelheid
Over a century ago, clinicians started to use the human amniotic membrane for coverage of wounds and burn injuries. To date, literally thousands of different clinical applications exist for this biomaterial almost exclusively in a decellularized or denuded form. Recent reconsiderations for the use of vital human amniotic membrane for clinical applications would take advantage of the versatile cells of embryonic origin including the entirety of their cell organelles. Recently, more and more evidence was found, showing mitochondria to be involved in most fundamental cellular processes, such as differentiation and cell death. In this study, we focused on specific properties of mitochondria of vital human amniotic membrane and characterized bioenergetical parameters of 2 subregions of the human amniotic membrane, the placental and reflected amnion. We found significantly different levels of adenosine triphosphate (ATP) and extracellular reactive oxygen species, concentrations of succinate dehydrogenase, and lactate upon inhibition of ATP synthase in placental and reflected amnion. We also found significantly different rates of mitochondrial respiration in isolated human amniotic epithelial cells and human amniotic mesenchymal stromal cells, according to the subregions. Differences in metabolic activities were inversely related to mitochondrial DNA copy numbers in isolated cells of placental and reflected amnion. Based on significant differences of several key parameters of energy metabolism in 2 subregions of vital amnion, we propose that these metabolic differences of vital placental and reflected amnion could have critical impact on therapeutic applications. Inclusion of region-specific metabolic properties could optimize and fine-tune the clinical application of the human amniotic membrane and improve the outcome significantly.